Mechanical circulatory support devices for patients with small anthropometric indicators - O. Yu. Esipova; A. S. Esipov; A. P. Kuleshov; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
Mechanical circulatory support (MCS) devices, designed specifically for patients with small anthropometric parameters, are now emerging. A detailed systematic literature review of existing systems for long-term circulatory support in this patient cohort was conducted. Circulatory support devices and their main technical and biological characteristics were studied in detail. Despite significant scientific and technological progress, there is still no technology for creating an assist pump to support patients with small body surface area (BSA), given the wide range of patient sizes, increased cardiovascular demand due to growth, as well as anatomical and physiological heterogeneity of congenital heart disease.